Assessment of Fusarium pseudograminearum and F. culmorum Biomass in Seedlings of Potential Host Cereal Species - Knight, Noel L; Sutherland, Mark W (Plant disease, 2017)
Fusarium crown rot is a major disease of wheat and barley worldwide, with the most frequently isolated causal agents being Fusarium pseudograminearum and F. culmorum. This study has successfully designed a quantitative polymerase chain reaction assay that is specific for F. culmorum, which has been used in conjunction with a previously established F. pseudograminearum-specific assay to compare the location and extent of infection by each fungus across a range of potential hosts, including six winter and three summer cereal species. All common winter cereals, excluding oat, demonstrated a similar range of visual and fungal biomass results when inoculated with either F. pseudograminearum or F. culmorum. Oat exhibited the lowest visual disease ratings and fungal biomass values of the winter cereals, while the sorghum, maize, and rice cultivars returned the lowest values overall. The ranking of host species according to visual discoloration was strongly correlated for both pathogens. Visual reactions to F. pseudograminearum were greater than those caused by F. culmorum in all potential hosts trialed; however, fungal biomass results only indicated this trend for barley. These results demonstrate significant variation in the ability of these pathogens to colonize the range of cereal species examined and also suggest differences between the pathogens in their patterns of host colonization.